Serum cardiac Troponin response in adolescents playing basketball - Nie, J.; Tong, T. K.; Shi, Q.; Lin, H.; Zhao, J.; Tian, Y. (International Journal of Sports Medicine, 2008)
Cardiac troponin release is generally found in adult athletes after continuous-type endurance exercises or sport competitions. The purpose of this study was to investigate whether the physical stress experienced by adolescents while playing basketball, an intense, intermittent-type sport, could induce transient elevations of the serum cardiac troponin T (cTnT) and I (cTnI). Serum cTnT and cTnI levels in 10 male adolescent players (age 15.0 ± 0.7 yr) were assessed immediately before and at 2, 4 and 24 h after a game randomly selected from a preseason basketball-training program. At 4 h following the game, serum cTnT levels in four of the ten subjects were above the cutoff of 0.01 ng · ml-1 for myocardial injury. Two of these four subjects had values higher than the acute myocardial infarction cutoff of 0.05 ng · ml-1. In three of the four subjects, the serum cTnI was above the cutoff of 0.06 ng · ml-1 for myocardial injury. Nevertheless, serum cardiac troponins at 24 h had returned to pre-exercise levels. These findings suggest that the physical stress encountered during intense, intermittent-type sports could cause release of cardiac troponins in some adolescents at low risk for cardiac disease.